Uniform and Stable Aerosol Jet Printing of Carbon Nanotube Thin-Film Transistors by Ink Temperature Control - Lu, Shiheng (ACS Appl Mater Interfaces, 2020)
Semiconducting carbon nanotube (CNT) networks exhibit electrical, mechanical, and chemical properties attractive for thin-film applications, and printing allows for scalable, economically favorable fabrication of CNT thin-film transistors (TFTs). However, device-to-device variation of printed CNT-TFTs remains a concern, which largely stems from variations in printed CNT thin-film morphology and resulting properties. In this work, we overcome the challenges associated with printing uniformity and demonstrate an aerosol jet printing process that yields devices exhibiting a hole mobility of μ(h) = 12.5 cm(2)/V · s with a relative standard deviation as small as 4% (from over 38 devices). The enabling factors of such high uniformity include control of the CNT ink bath temperature during printing, ink formulation with nonvolatile and viscosifying additives, and a thermal treatment for polymer removal. It is discovered that a low CNT ink temperature benefits aerosol jet printing uniformity and stability in both short-term (~1 min) and long-term (~1 hour) printing settings. These findings shed light on the effect of a commonly overlooked dimension of CNT aerosol jet printing and provide a practical strategy to large-scale, high-consistency realization of CNT-TFTs.